A‐IGZO TFT Based Operational Amplifier and Comparator Circuits for the Adaptive DC‐DC Converter. Issue 1 (June 2014) - Kim, Kichan; Choi, Keun‐Yeong; Choi, Dong‐Hyuk; Lee, Hojin
Abstract In this paper, we present an operational amplifier (op‐amp) based on amorphous Indium‐Gallium‐Zinc‐Oxide thin‐film transistors (a‐InGaZnO TFTs) to achieve a comparator operated by pulse‐width‐modulation (PWM) control‐loop structure, which can be used for dc‐dc converter circuits integrated in the display driving system. Based on electrical characteristics of the fabricated a‐InGaZnO TFT, we proposed a novel NMOS op‐amp to achieve the overall gain of 19.2dB. On the basis of the proposed op‐amp, we fabricated a‐InGaZnO TFT comparator circuit, which could successfully operate at 100 Hz to control the duty ratio from 25% to 75% with the slew rate of 0.625V/μs.